CONSTRUCTION OF A CONVERGENCE COMMUNICATION MODEL: HARMONIZATION OF SOCIAL AND DIGITAL CAPITAL IN CROSS-GENERATIONAL AGRICULTURAL COLLABORATION - Agus Kristian; Eko Purwanto (CV. Radja Publika, 2026)
The global agricultural sector currently faces a serious threat in the form of a farmer regeneration crisis amidst the ambition to achieve sustainable food security. Although Smart Farming technology is readily available, its adoption rate is hampered by a sharp communication gap between senior farmers and the younger generation. This study aims to construct a convergence communication model capable of harmonizing the social capital of senior farmers and the digital capital of the younger generation. The method used is a qualitative systematic literature review approach . The analysis was conducted on various reputable literature from the Scopus, Web of Science, and Sinta databases spanning the past ten years. The results show a divergence in characteristics between the bonding social capital of senior farmers, which tends to be exclusive, and the digital capital of the younger generation, which is technocentric but lacks social relations. As a solution, this study constructs a Convergence Communication Model that integrates reverse mentoring strategies and cyclical dialogue to achieve mutual understanding . The implications of this model are the creation of an inclusive acceleration of farmer regeneration, increased resource efficiency based on a green economy , and strengthened national food stability through resilient intergenerational asset synergy.